MENINGKATKAN KEMAMPUAN KOMUNIKASI MELALUI PEMBELAJARAN KOOPERATIF TIPE TARI BAMBU - Idham Kholid; Dede Rohaniawati (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This research was conducted with the aim to know the application of cooperative learning model of bamboo dance type in learning social studies in every cycle and to know the improvement of student communication skill in every cycle. The method used in this research is classroom action research. Students who made the object of this study is the fifth-grade students of Islamic primary school AlMuawwanah in Subang District West Java Indonesia, which amounted to 30 consisted of 21 men and 9 women. The data collection techniques using teacher and student observation sheets and performance assessment sheets. The results of this study showed that the application of cooperative learning model of bamboo dance type can improve students' communication skills. The result of precycle student communication skill assessment is 42,83%. In the first cycle increased by 56.83% and more increased in cycle II reached 66.67%. The highest achievement occurred in the third cycle of 86.17%. This study shows that communication skill of grade 5 students of Islamic primary school in Al-Muawwanah has increased during the implementation of cooperative learning model of bamboo dance type in each cycle. The activities of teachers and students in the learning process also increased in every cyle.